Persepsi Masyarakat Kth Buttu Puang Untuk Pengembangan Budidaya Trigona Sp. Di Desa Mirring Kabupaten Polman - Daud Irundu; Fitri Indhasari Indhasari; Widyanti Utami; Sartika Sartika (Program Studi Kehutanan Universitas Muslim Maros, 2023)
Perception is a source of basic information in efforts to develop Trigona sp. honey bee cultivation. This study aims to determine the perceptions of the KTH buttu Puang community in the effort to develop Trigona sp honey bee cultivation in Mirring Village, Binuang District, Polewali Mandar Regency, West Sulawesi Province. The method used is interviewing 30 people who are members of KTH Buttu Puang. The data obtained were analyzed descriptively to determine attitudes and levels of understanding. The results showed that in order to develop Trigona sp. beekeeping. most of the people have an attitude of strongly agree (69.80%) and strengthened by the attitude of agreeing as much as 28.57%. However, there were also those who answered that they did not agree at 1.63%. The level of understanding of the KTH Buttu Puang community based on high, medium and low levels of understanding respectively 56.7%; 25.0%; and 18.3%.